2019
DOI: 10.1016/j.arthro.2019.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Superior Capsule Reconstruction: Grafts for Superior Capsular Reconstruction Must Be Thick and Stiff

Abstract: To achieve a good functional outcome, including minimal graft tear, after superior capsule reconstruction, surgeons should carefully compare the biomechanical properties of all graft materials under consideration. In particular, graft stiffness affects postoperative stability in the glenohumeral joint, acromiohumeral distance, and graft healing. In my experience, a sufficiently stiff fascia lata graft is 6-to 8-mm thick and includes suture reinforcement and/or an augmentation patch. I believe that augmenting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…4,6,21,23,28,40,50 Graft healing is already known to be essential in achieving maximum shoulder function and minimizing rotator cuff arthropathy. 10,[32][33][34][35][36] Mihata et al 36 showed an average increase of 4.1 mm in AHD at the final follow-up, which corresponded to graft thickness; these outcomes have been confirmed as key factors in restoring the superior stability of the shoulder joint. 32,33,35,37 To decrease the graft failure rate, a thick graft (6-8 mm) with suture reinforcement has been suggested to enhance stiffness.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…4,6,21,23,28,40,50 Graft healing is already known to be essential in achieving maximum shoulder function and minimizing rotator cuff arthropathy. 10,[32][33][34][35][36] Mihata et al 36 showed an average increase of 4.1 mm in AHD at the final follow-up, which corresponded to graft thickness; these outcomes have been confirmed as key factors in restoring the superior stability of the shoulder joint. 32,33,35,37 To decrease the graft failure rate, a thick graft (6-8 mm) with suture reinforcement has been suggested to enhance stiffness.…”
Section: Discussionmentioning
confidence: 91%
“…32,33,35,37 To decrease the graft failure rate, a thick graft (6-8 mm) with suture reinforcement has been suggested to enhance stiffness. 33 However, as noted by surgeons who performed ASCR, shuttling and intra-articular manipulation of the graft are challenging, particularly when a thicker graft is involved. Hence, we proposed a surgical modification to augment grafts with polypropylene mesh to provide sufficient graft stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 , 26 , 27 The surgeons using FLA usually recommend 6- to 8-mm thickness of the graft. 25 , 28 , 31 , 43 Mihata et al. 44 compared the biomechanical properties of 3 mm thick dermal allograft with an 8-mm FLA in a shoulder cadaver model.…”
Section: Discussionmentioning
confidence: 99%
“…They usually add 5 to 10 mattress sutures in the body of the graft to achieve the sufficient stiffness. 43 In our study, we chose nonresorbable suture mesh of high tensile strength to reinforce the graft. The reinforcement led to a strong and stiff FLA with the desirable thickness, without harvesting a large portion of the fascia lata.…”
Section: Discussionmentioning
confidence: 99%